Lipophilic antioxidants in blood plasma as markers of atherosclerosis: the role of α-carotene and γ-tocopherol - Kontush, Anatol; Spranger, Torsten; Reich, Axel; Baum, Katja; Beisiegel, Ulrike (Atherosclerosis, 1999)
Oxidative theory of atherosclerosis implies that plasma levels of lipophilic antioxidants might serve as indicators of lipoprotein oxidation in the arterial wall and as markers of the development of atherosclerosis. However, it is unknown whether the measurement of plasma antioxidants is able to reflect atherogenesis or its risk. In order to assess whether the levels of lipophilic antioxidants in human plasma can discriminate between subjects with and without atherosclerosis, we measured the lipophilic antioxidants α-tocopherol, γ-tocopherol, α-carotene, β-carotene and ubiquinol-10 in plasma of 34 patients with coronary heart disease (CHD) and in 40 control subjects. We found that α-carotene and γ-tocopherol were significantly lower in plasma of CHD patients compared to controls. This decrease was significantly independent of whether the antioxidants were expressed as its absolute amounts in plasma ( P<0.001 for α-carotene, and P=0.001 for γ-tocopherol) or normalized to plasma lipids ( P<0.001 for both). In contrast, β-carotene was only lower in plasma of CHD patients in comparison to controls, when normalized to the lipids ( P=0.02). Independent contributions of different parameters to the variation in these plasma antioxidants were estimated using multiple regression approach. The analysis showed that both the decrease in α-carotene and the decrease in γ-tocopherol were significantly associated only with the presence of CHD ( P<0.001 for each regression), while the decrease in β-carotene was significantly related to the presence of hyperlipidaemia ( P<0.001). In striking contrast, no decrease in plasma α-tocopherol and ubiquinol-10 was detected in the patient group independently of how these antioxidants were expressed. These data suggest that plasma levels of α-carotene and γ-tocopherol may represent markers of atherosclerosis in humans. Measuring these antioxidants may be of clinical importance as a practical approach to assess atherogenesis and/or its risk.